Predicting TSE transmission - Manson, Jean (Henry Stewart Talks, 2008)
The TSEs continue to pose a problem to animal and human health, The vCJD epidemic appears to be in decline but new risks of human to human transmission are now apparent, Chronic wasting disease is a major problem currently in the US although its presence has not yet been detected in Europe, Predicting and preventing transmission of disease requires an understanding of the routes of transmission within and between animals and the host factors which determine susceptibility, We have studied natural disease and both in vivo and in vitro model systems to unravel the basic mechanisms of disease, PrP protein has a central role in the outcome disease and mutations and polymorphisms in host PrP can profoundly alter the host's susceptibility to a TSE agent, Precisely how host PrP influences the outcome of disease has not been established, Both mutations and glycosylation can profoundly influence transmission both within and between species
Archived at 2021/02/25